Evaluasi Sistem Informasi Akuntansi Piutang Untuk Meningkatkan Efektivitas Pengendalian Piutang Berbasis Aplikasi EXA Pada PT ABC - Dilla Windi Natasya; Risawati Risawati (Penerbit Jurnal Indonesia, 2026)
Ineffective receivables management can disrupt a company's liquidity and financial stability, especially in those with high credit sales volumes. PT ABC has implemented a receivables accounting information system based on the EXA application, but during implementation, various obstacles have been identified that affect the effectiveness of receivables control. This research aims to evaluate the current accounts receivable accounting information system and formulate recommendations to improve the effectiveness of receivables control at PT ABC. The research uses a descriptive approach with a case study method. Data was obtained through interviews, observation and documentation related to the process of recording, controlling and reporting receivables. The research results show that the system used does not fully support optimal receivables control, as evidenced by late billing, weak maturity monitoring, limited control over transaction approvals, and inadequate use of receivable aging reports. Evaluation and recommendations for improving the EXA application include strengthening the approval flow, automatically notifying of overdue receivables, limiting access rights, and presenting more informative accounts receivable reports. Implementing these recommendations can improve recording accuracy, speed up the billing process, and strengthen the receivables control function. This research shows that evaluating application-based accounts receivable accounting information systems plays an important role in supporting the effectiveness of company receivables control.